Supervision Strategies for Improving Learning Outcomes in Islamic-Based General Education Institutions - Tri Yuli Lestari; Fisman Bedi (Journal of Islamic Education Research, 2025)
This study examines the supervision strategies as a strategy to enhance learning outcomes at SMK Muhammadiyah 1 Purwokerto, adopting a distinct approach compared to previous studies that primarily focus on general learning supervision. The research aims to explore the impact of academic supervision on learning quality. Utilizing a qualitative field research method, the study involved direct observations and interviews with the Principal, Vice Principal for Curriculum, Vice Principal for Student Affairs, and teachers. Data were analyzed using the Miles and Huberman model, comprising data reduction, data display, and conclusion verification. The findings reveal that academic supervision, implemented through both group and individual methods, effectively enhances learning quality and teacher competence. This improvement is reflected in better student achievement, increased cooperation skills, a more conducive learning environment, contextualized learning processes, and the attainment of curriculum objectives. Moreover, academic supervision serves as a professional development tool, enabling teachers to adapt more effectively to student needs and the evolving demands of modern learning methods.